The Anthropocene and anthropology - Hann, Chris (European Journal of Social Theory, 2017)
Noting a lack of consensus in the recent literature on the Anthropocene, this article considers how social anthropologists might contribute to its theorizing and dating. Empirically it draws on the author’s long-term fieldwork in Hungary. It is argued that ethnographic methods are essential for grasping subjectivities, including temporal orientations and perceptions of epochal transformation. When it comes to historical periodization, however, ethnography is obviously insufficient and proposals privileging the last half-century, or just the last quarter of a century, seem inadequate. Influential theories, which define ‘modernity’ in terms of developments emanating from the countries of the North Atlantic in the sixteenth to the nineteenth centuries (Gellner, Polanyi, Wolf), remain partial and Eurocentric. To comprehend the social preconditions of the Anthropocene in a holistic fashion (the crucial contribution of comparative anthropology), it is necessary to follow Jack Goody and trace how the urban revolutions of the Bronze Age united Eurasia through the diffusion of new forms of economy, polity and cosmology.
Anthropology
Keywords: Eurasia; GOODY; Jack; 1919-2015; Hungary; anthropocene; anthropocene epoch; anthropology; cosmology; ethnology; social anthropology; socialism